ANALYSIS OF JOHN RAWLS PERSPECTIVE OF JUSTICE VALUE ON BARTER MARKET IN LAMALERA VILLAGE - Raimundus Bulet Namang (Universitas PGRI Madiun, 2020)
This journal examines how justice takes place in the barter market in Lamalera village from the perspective of justice John Rawls. There are values of justice that occur in the barter market in Lamalera village which has become a sacred value that has been believed for generations. According to John Rawls, the principle of equality states that everyone has the same right to the most basic basic freedoms, as wide as the same freedoms for all people. Or in other words everyone has the same rights to the whole system of equal human rights and is accessed by everyone. This principle regulates the application of rights and obligations and regulates the distribution of social and economic benefits. The principle of equality of fairness makes all social arrangements lead peaceful lives. The barter market in Lamalera village shows how justice and family values are created. The market system which has been a legacy of ancestors and is still preserved or still preserved up to now with values that are already considered sacred because it is a noble heritage of ancestors. Limited economic conditions require the people of Lamalera to operate a barter market by instilling the values of justice, family and socialist values which are indicated by mutual agreement in the exchange of goods for goods.